Kajian Penggunaan Incinerator Untuk Mengelola Limbah Medis Padat di Denpasar - Adiputra, I.G.A.B.; Giriantari, I.G.A.D.; Kumara, I. N. S. (Majalah Ilmiah Teknologi Elektro, 2019)
One method to process toxic waste of hospital is incinerator. An incinerator burns hospital toxic waste at high temperatures. Many hospitals have to transport their toxic waste to rhid party location which often far away. In Bali, there are 62 hospitals with 6.195 beds with 5.584.310 annual visits from patients from patients and therefore generate large amount of toxic waste. Hospitals in Bali have to send their waste to incinerators in other island a few thousand kilometres away. This practice is expensive and add more environmental problems due to emmisions from transport vehicle and traffic congestion on the Java to Bali land transports. One solution is to develop small sclae incinerator near hospital’s site. This paper discuses the development of small incinerator in Denpasar city of Bali covering insvestment, performance metric, and economical feasibilty. The project is funded by international aid and currently the only incinerator on the island. Description of the plant component, environmental metric, investment analysis Keywords — Hospital, waste treatment, toxic waste, incinerator, environmental, economical feasibility, NPV, payback period, energy conservation.